Learning and building technological capabilities of enterprises through links with foreign partners: some international experiences and Vietnam practice - Ca, Tran Ngoc; Thao, Tang Thu; Tung, Dang Thanh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
The study is focused on enhancement of national technological capabilities, enterprise technological capabilities and learning process to accumulate these capabilities. Some international experiences show that, among the channels fortecnological learning, the one connecting to foreign partners is on the top of the most effective ways. In the new context of fast going changes in international economic relations and technological development, the process of learning from international partners may need to change but the process remains the most effective tool as it is shown by practice of some enterprises in processing and manufacturing sectors of Vietnam through conducted surveys. The study also offers a proposal of certain policies to promote the process of technological learning applicable for Vietnam enterprises. Code: 18092501